Digital reconstruction as an alternative to perfunctory restoration; a case study of Sompur Mahavihara at Paharpur in Bangladesh - Rashid, Md. Mizanur (2011)
The 8th century monastery of Sompur Mahavihara at Paharpur, Bangladesh, which has been listed as a UNESCO World Heritage (WH) Site since 1985, are the earliest evidence of monumental architecture in Bengal. After the inscription on the WH List, a major conservation program for the site was undertaken. The present state of the monastery has raises some serious questions about the appropriateness of the conservation work being done and concerns the professionals and scholars who are interested in the monument. This paper would examine critically the recently undertaken conservation /reconstruction attempt and tries to identify it might destroy the heritage value of the monuments. At the same time this would solicit some other ways of conserving the heritage and its demand to the common people.